Existence and multiplicity of periodic solutions for a generalized hematopoiesis model - Amster, Pablo Gustavo (2017)
A generalization of the nonautonomous Mackey–Glass equation for the regulation of the hematopoiesis with several non-constant delays is studied. Using topological degree methods we prove, under appropriate conditions, the existence of multiple positive periodic solutions. Moreover, we show that the conditions are necessary, in the sense that if some sort of complementary conditions are assumed then the trivial equilibrium is a global attractor for the positive solutions and hence periodic solutions do not exist.